Pengaruh Content Marketing dan Influencer Marketing Terhadap Keputusan Pembelian Smartphone Xiaomi Melalui E-WOM Sebagai Variabel Intervening di Daerah Istimewa Yogyakarta - Akram Shofwan Setiawan; Uswatun Chasanah (Economic Reviews Journal, 2025)
This study uses e-WOM as an intervening variable to determine how Content Marketing and Influencer Marketing influence purchasing decisions. The research methodology used in this study is quantitative. The population in this study used customers who had purchased Xiaomi smartphone products in the Special Region of Yogyakarta with a sample of 100 respondents using purposive sampling technique. This study uses an analytical tool in the form of SmartPLS version 4 with data analysis methods such as Convergent Validity, Discriminant Validity, Average Variance Extracted (AVE), Composite Reliability, Cronbach's Alpha, R-Square, Goodness of Fit, and Hypothesis Test. The results showed that Content Marketing has no influence on Purchasing Decisions while Influencer Marketing and e-WOM have an influence on Purchasing Decisions. On the other hand, Content Marketing and Influencer Marketing have an influence on e-WOM. Furthermore, e-WOM can fully mediate the effect of Content Marketing on Purchasing Decisions while e-WOM can pseudo-mediate the effect of Influencer Marketing on Purchasing Decisions.